The performance of future wireless communication systems - Liu, Y (2011)
Multimedia services provided through wireless networks, such as mobile television and video calls, have recently attracted great attention. These systems require higher data rates, better communication quality, and wider channel bandwidth compared with traditional wireless network services, such as voice calling and text messaging. In response to these demands, multiple-input multiple-output (MIMO) employing multiple antennas at both transmitter and receiver, has been investigated in recent years. Nevertheless, the major impediment in MIMO based wireless systems is the cost of the hardware due to the requirement of the complete radio frequency (RF) chain for each transmit and receive path. One technique named antenna subset selection has been proposed which can reduce the hardware complexity, for example, provide and smaller number of RF chains which are reconfigurable to serve multiple antennas, but retain good communication performance, such as increasing data rates and improving communication quality. On the other hand, network service providers have in recent years established wideband communication systems in order to provide more services and higher bandwidth to customers. However, this development lowers the communication link quality, since signals transmitted in wideband communication systems suffer frequency-selective fading. In order to reduce the fading, orthogonal frequency division multiplexing (OFDM) as a potential infrastructure in the fourth generation mobile communication networks is developed. Referring to the cost-performance ratio, an attractive future wireless system named antenna selection based MIMO-OFDM is considered to be widely utilized in civil wireless communications in near future. The working theory of antenna selection based MIMO-OFDM systems can be simply represented as that a data stream at each selected transmit/receiver antenna is sent/receive over a number of narrow band orthogonal subcarriers. This thesis addresses analysis of wireless channel and performance investigation of future wireless communication systems, such as MIMO and OFDM structures. Moreover, a novel significantly low computational complexity algorithm is introduced in this thesis, which is proposed for antenna selection MIMO-OFDM systems on the basis of multiple selection criteria. It is shown that the proposed selection algorithm clearly reduces the computational complexity load of the selection process and efficiently selects the optimum antenna subset of antenna selection MIMO-OFDM systems. The thesis concludes by outlining the advantage of the proposed antenna selection technique and points out its potential role in future wireless communications.